Скіфська антропоморфна стела із Запоріжжя - Остапенко, М.А.; Панченко, І.В. (Археологія, 2014)
Публікується кам’яна скіфська стела, випадково виявлена в районі Запоріжжя. В 2011 г. в с. Ручайовка недалеко от г. Запорожье случайно была выявлена антропоморфная стела, переданная в Национальный заповедник «Хортица». Ее происхождение не установлено. Возможно, стела связана со скифскими курганами региона, на что указывает ее материал.
Стела изготовлена из крохкого серокоричневого гранита. Верх обломан. Сохранившаяся высота 2,18 м, толщина сверху 0,35 × 0,32 м, внизу 0,60 × 0,52 м. Она представляет фигуру мужчины с разными аксесуарами. На груди выгравированы два кружка (видимо, передают бляхи); в правой руке воин держит ритон; к поясу с правой стороны подвешены акинак, топор-клевец и горит. На тыльной стороне, видимо, отмечены детали одежды.
Ориентировочно стела датируется VI в. до н. э. In 2011, in ruchaivka village not far from Zaporizhzhia, an anthropomorphous stele was found accidentally and passed to the national Preserve «khortytsia». Its origin is not determined. Perhaps, the stele is related with the scythian barrows in the region which is evidenced by its material.
the stele is made of porous grey and brown granite. Its upper part is broken off. Its preserved height is 2,18 m, thickness in the upper part is 0,35 × 0,32 m and in the lower part is 0,60 × 0,52 m. It presents a figure of a man with accessories. two circles are engraved on his breast, apparently, representing metal plates; in his right hand a warrior is holding a rhyton; an acinaces, a horseman’s pick, and a gorytos are hanged up to the right part of his belt. evidently, the clothes details are marked on the backside.
the stele is dated roughly by the 6th c. Bc.